12 rules for life an antidote to chaos - Peterson, Jordan B; Doidge, Norman; Van Sciver, Ethan (Toronto Random House Canada, 2018)
"What does everyone in the modern world need to know? Renowned psychologist Jordan B. Peterson's answer to this most difficult of questions uniquely combines the hard-won truths of ancient tradition with the stunning revelations of cutting-edge scientific research. Humorous, surprising and informative, Dr. Peterson tells us why skateboarding boys and girls must be left alone, what terrible fate awaits those who criticize too easily, and why you should always pet a cat when you meet one on the street. What does the nervous system of the lowly lobster have to tell us about standing up straight (with our shoulders back) and about success in life? Why did ancient Egyptians worship the capacity to pay careful attention as the highest of gods? What dreadful paths do people tread when they become resentful, arrogant and vengeful? Dr. Peterson journeys broadly, discussing discipline, freedom, adventure and responsibility, distilling the world's wisdom into 12 practical and profound rules for life. [This book] shatters the modern commonplaces of science, faith and human nature, while transforming and ennobling the mind and spirit of its readers."--
Stand up straight with your shoulders back -- Treat yourself like someone you are responsible for helping -- Make friends with people who want the best for you -- Compare yourself to who you were yesterday, not to who someone else is today -- Do not let your children do anything that makes you dislike them -- Set your house in perfect order before you criticize the world -- Pursue what is meaningful (not what is expedient) -- Tell the truth--or, at least, don't lie -- Assume that the person you are listening to might know something you don't -- Be precise in your speech -- Do not bother children when they are skateboarding -- Pet a cat when you encounter one on the street
"Issued in print and electronic formats"--Title page verso
Includes bibliographical references (pages 371-389) and index
1
Keywords: Conduct of life -- Philosophy; PHILOSOPHY -- Social; PSYCHOLOGY -- Applied Psychology; SELF-HELP -- Personal Growth; Conduct of life -- Philosophy; Conduct of life